ChemInform Abstract: Solvent‐ and Ligand‐Free Palladium‐Catalyzed Amination of Aryl Halides. Issue 16 (22nd April 2014) - Basolo, Luca; Bernasconi, Alice; Broggini, Gianluigi; Gazzola, Silvia; Beccalli, Egle M.
Abstract The reaction proceeds under microwave‐assisted conditions, reaction times are not given.